PERANAN STAF KOMISI DALAM MENUNJANG AKTIVITAS KEGIATAN KOMISI DI DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN MERANTI - jurnalmap map; Efriyadi ÔÇÄ; Hadi Susanto; Esa Wahyu Endarti (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2021)
The aim of the study is to present a comprehensive description of the role of staff, the factors that support the role of administration and political access and recommend an effective role of administration in supporting the activities of the commission in the Regional House of Representatives of Meranti Regency. This study uses a descriptive method with a qualitative approach. The focus of the study in this research is the administrative role and political access of commission staff at the Meranti Regency Regional People's Representative Council which is carried out formally and informally. The research includes the role of commission staff, factors that support the role of administration and political access and recommendations for the effectiveness of the administrative role and political access of commission B (Economy) staff in the Regional House of Representatives of Meranti Regency. Developments and environmental changes in political life have colored the attitude of relations between the legislative and executive bodies in the past towards the opinion that DPRD commission staff are only limited to being part of local government. This gave rise to a discourse that the existence of the DPRD Commission B staff at that time as staff who followed the orders of the members of the council wherever the members of the council held plenary meetings, work visits or others.